JAQSÍLÍQ HÁM JAMANLÍQ KONCEPTLERINIŃ AQ HÁM QARA REŃLERDE BERILIWI - Bekbosinova, G.M. (SCIENCE and SOCIETY, 2025)
The article provides comments on the participation of black and white colors in the Karakalpak language in the composition of connotative semantic units that have both positive and negative connotation, which serve to ensure the effectiveness of speech.